Methodes iteratives pour les fluides incompressibles - Hadji, Sofiane; Dhatt, Gouri (European Journal of Computational Mechanics, 1977)
This paper presents an overview of different iterative methods Conjugate gradient (CG), Biconjugate gradient (BfCG), conjugate gradient squared (CGS), Biconjugate gradient stabilized (BfCGSTAB), transpose{ree quasi minimal residual (TFQMR), full orthogonal method (FOM) et Generalized minimal residual (GMRES) for solving finite element systems of Navier-Stokes incompressible flows. To accelerate convergence of those methods, preconditio11ner based on incomplete Gauss factorisation (fLU) is used. The accent is put on the necessity to renumber the unknowns to guaranty the convergence of the iterative methods. The importance of a variable stop criterion of iterative methods for each Newton-Raphso/1 step is underlined.